Real-world comparison of clopidogrel, prasugrel and ticagrelor in patients undergoing primary percutaneous coronary intervention. Issue 1 (29th June 2019) - Krishnamurthy, Arvindra; Keeble, Claire; Anderson, Michelle; Somers, Kathryn; Burton-Wood, Natalie; Harland, Charlotte; Baxter, Paul; McLenachan, Jim; Blaxill, Jonathan; Blackman, Daniel J; Malkin, Christopher; Wheatcroft, Stephen; et al.
Abstract : Background: There is a paucity of real-world outcome data comparing clopidogrel, prasugrel and ticagrelor in primary percutaneous coronary intervention (PPCI) for ST-segment elevation myocardial infarction (STEMI). We sought to assess the association of choice of oral P2Y12-receptor inhibitor with clinical outcomes following PPCI for STEMI in a large consecutive patient series. Methods: Demographic, procedural and 12-month outcome data were prospectively collected for all patients undergoing PPCI in Leeds, UK, between 01 January 2009 and 31 December 2011, and 01 January 2013 and 31 December 2013. Clinical endpoints were 30-day and 12-month all-cause mortality, recurrent MI and 30-day HORIZONS-major bleeding. Logistic regression analyses were undertaken to adjust for confounding factors. Results: Prasugrel (n=1244) was associated with lower adjusted 30-day (OR 0.53 (0.34–0.85)) and 12-month (OR 0.55 (0.38–0.78)) mortality, and 12-month MI (OR 0.63 (0.42–0.94)) compared with clopidogrel (n=1648). Importantly, prasugrel was associated with lower adjusted 30-day mortality (OR 0.51 (0.29–0.91)) compared with ticagrelor (n=811). Lower 30-day (OR 0.40 (0.17–0.94)) and 12-month (OR 0.54 (0.32–0.93)) MI were observed in ticagrelor compared with clopidogrel, an association absent in comparison with prasugrel. Adjusted bleeding were not statistically significantly different among the P2Y12-receptor inhibitors. Conclusion: In this large consecutive real-world series, prasugrel was associated with lower adjusted 30-day mortality compared with ticagrelor and clopidogrel, and lower adjusted 12-month mortality compared with clopidogrel. Both prasugrel and ticagrelor were associated with lower recurrent MI following PPCI compared with clopidogrel, with no overall increase in adjusted bleeding.